The EU, Russia and Models of International Society in a Wider Europe - Andrey Makarychev; Alexander Sergunin (Journal of Contemporary European Research, 2013)
The research objective of this article is two-fold: On the one hand, this study aims at analysing the multifaceted EU-Russia relations as seen from different theoretical/conceptual approaches. On the other hand, this article examines how the EU-Russia dialogue is organised in sectoral terms – economy, trade, visa regime liberalisation, and security cooperation. Both the promising and problematic areas in the EU-Russia bilateral relations are identified. The need for a more adequate conceptual framework applicable to the EU-Russia relations as well as a new, more efficient, EU-Russian joint strategy is explained.